VISUALIZATION OF THE EXCITATION PROCESS IN THE FROG'S NERVES - N. V. KORNILOVA; V. G. ABUSHKEVICH; A. N. ARDELYAN; Yu. Yu. PEROVA; A. G. POKHOT'KO (Кубанский научный медицинский вестник)
Aim. Visualization of the excitation process in the frog's nerves.Materials and methods. Observations were carried out on 30 immobilized frogs. Vagosympathetic trunks and sciatic nerve were  allocated from the frogs. Ligatures were placed on the right  vagosympathetic trunk crossing it. A scanner of the gas discharge  visualization camera of the CELSY device, which created a high- frequency electromagnetic field (1024 Hz), was installed above the  nerves. The scanner with a highly sensitive camera shot a 60-second video (the frequency of frame-by-frame shooting to 1000 frames per second), during which the edge luminescence (Kirlian effect) and the  glow spots were recorded inside the nerve. The  electrocardiogram (ECG) was synchronously recorded in the I  standard lead. The processing of the obtained results was carried out according to the area of the glow spot, the area of the highest luminescence brightness, the direction of the movement of  the foci of the luminescence, and the linear velocity of the movement of the glow foci.Results. Foci of the internal luminescence appeared only in the high-frequency electromagnetic field in the sciatic nerve of the frog  when the nerve was stimulated by electrical impulses, which resulted in the contraction of the frog's foot. Glow foci of the brain  synchronous to the heart rhythm and preceding the tooth of the V- wave on the frog’s ECG were observed at the central end of the cut  of the frog’s vagosympathetic trunk. Conclusion. Visualized foci of luminescence in the nerve reflect the neural activity.